Processing of DNA Ends in the Maintenance of Genome Stability - Bonetti, Diego; Colombo, Chiara Vittoria; Clerici, Michela; Longhese, Maria Pia (Frontiers in Genetics, 2018)
DNA double-strand breaks (DSBs) are particularly hazardous lesions as their inappropriate repair can result in chromosome rearrangements, an important driving force of tumorigenesis. DSBs can be repaired by end joining mechanisms or by homologous recombination (HR). HR requires the action of several nucleases that preferentially remove the 5’-terminated strands at both DSB ends in a process called DNA end resection. The same nucleases are also involved in the processing of replication fork structures. Much of our understanding of these pathways has come from studies in the model organism Saccharomyces cerevisiae. Here, we review the current knowledge of the mechanism of resection at DNA DSBs and replication forks.